Carbon footprint impact of the choice of inhalers for asthma and COPD. Issue 1 (7th November 2019) - Janson, Christer; Henderson, Richard; Löfdahl, Magnus; Hedberg, Martin; Sharma, Raj; Wilkinson, Alexander J K
Abstract : In the 1990s, metered dose inhalers (MDIs) containing chlorofluorocarbons were replaced with dry-powder inhalers (DPIs) and MDIs containing hydrofluorocarbons (HFCs). While HFCs are not ozone depleting, they are potent greenhouse gases. Annual carbon footprint (CO2 e), per patient were 17 kg for Relvar-Ellipta/Ventolin-Accuhaler; and 439 kg for Seretide-Evohaler/Ventolin-Evohaler. In 2017, 70% of all inhalers sold in England were MDI, versus 13% in Sweden. Applying the Swedish DPI and MDI distribution to England would result in an annual reduction of 550 kt CO2 e. The lower carbon footprint of DPIs should be considered alongside other factors when choosing inhalation devices.